Gardening; OFFICE PLANTINGS RISE IN CORPORATE WORLD - Totemeier, Carl (The New York times, 1981)
Richard Parker, who supervised this planting, pointed out that many new hotels include plants in the guest rooms. If the maintenance man comes around to water the plants while the ''do not disturb'' sign is out, the plant must do without. For other reasons, plantings, in public buildings are subject to harsher conditions than occur in most homes. It would sound too good to be true that a planting that includes Kentia palms, Dracena massangeana, Spathyphyllum, Ficus benjamina, Shefflera, Philodendron selloum, Dracena marginata, Chinese evergreen, Boston fern and grape ivy could be watered with a troublefree automatic system, but this would seem to be the case. The system consists of a plastic reservoir tank buried in the soil beneath the plant root. A tube extends from above the surface of the soil into the tank and allows for filling and provides a means of allowing air to reach the plant roots. The lid of the tank is perforated, so that the air can readily diffuse into the soil. Within the lid are one or more depressions filled with soil during planting. They extend beneath the water level within the tank and serve as a wick for the absorption of water. The water then is drawn upward by capillary action to keep the soil around the roots uniformly moist but not too wet - the ideal moisture situation for any plant from cacti to shefflera.